Effect of Topical Mitomycin C as an Adjunct to Dilation Therapy in Esophageal Strictures - Zunaira Hameed; Muhammad Tariq Aziz; Muhammad Aslam Sheikh; Saima Jabeen Joiya (ziauddin University, 2024)
Background: The treatment of choice for most esophageal strictures is esophageal dilatation but it has a low success rate. This study was conducted to determine the effect of topical mitomycin C as an adjunct to dilatation therapy in esophageal strictures among children. Methods: This randomized controlled trial was conducted at the Department of Pediatric Gastroenterology, The Children's Hospital and Institute of Child Health, Multan, Pakistan, from July 2022 to October 2023. Children aged 1-12 years and having esophageal strictures were included. A simple random sampling technique was adopted. Children in the Mitomycin C group received topical mitomycin C (2 mg/20 ml saline) during the endoscopy, whereas the placebo group received normal saline. The counts of dilatation sessions necessary in each group and the proportion of patients who were symptom-free after 12 months of therapy were noted (outcome). IBM-SPSS 26 was used for data analysis with p<0.05 considered significant. Results: In a total of 76 children, 52 (68.4%) were male. Overall, the mean age was 4.49±1.96 years. The mean age in mitomycin C (n=38) and placebo group (n=38) were 4.85±1.67 years and 4.25±2.27 years, respectively (p=0.1934). After 12 months, patients in the mitomycin C group had a considerably greater rate of therapeutic success than placebo patients did at 12 months follow-up (84.2% vs. 47.4%; p=0.0007). The average number of dilatation sessions needed was considerably lower in the experimental group than in the control group (2.05±0.78 vs. 3.18±1.54, p<0.0001). Conclusion: Topical mitomycin C when combined with endoscopic dilatations, resulted in much improved outcomes in children with esophageal strictures. Keywords: Dilation, Dysphagia, Esophageal Strictures, Mitomycin C, Placebo, Topical.